Matrix approach to solve polynomial equations - Samir Brahim Belhaouari (9427347) (2023)
Polynomials are widely employed to represent numbers derived from mathematical operations in nearly all areas of mathematics. The ability to factor polynomials entirely into linear components allows for a wide range of problem simplifications. This paper presents and demonstrates a novel straightforward approach to solving polynomial problems by converting them to matrix equations. Each polynomial of degree n can be decomposed into a sum of degree ⌈n/2⌉ polynomials squared. Other Information Published in: Results in Applied Mathematics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.rinam.2023.100368